2023
DOI: 10.1007/s00423-023-02913-5
|View full text |Cite
|
Sign up to set email alerts
|

Is preoperative sarcopenia associated with postoperative complications after pelvic exenteration surgery?

Abstract: Purpose Pelvic exenteration (PE) involves radical surgical resection of pelvic organs and is associated with considerable morbidity. Sarcopenia is recognised as a predictor of poor surgical outcomes. This study aimed to determine if preoperative sarcopenia is associated with postoperative complications after PE surgery. Methods This retrospective study included patients who underwent PE with an available preoperative CT scan between May 2008 and No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…This study also found that patients who underwent combined gastrointestinal surgery had a higher incidence of postoperative hypoproteinemia. One of the reasons is that managing concomitant gastrointestinal surgery in these patients requires longer operating times, causing increased energy consumption and increased breakdown of plasma albumin [17] . Additionally, more uids need to be administered, leading to further dilution of plasma albumin [18] .…”
Section: Comparison Of Preoperative Data Between the Two Groupsmentioning
confidence: 99%
“…This study also found that patients who underwent combined gastrointestinal surgery had a higher incidence of postoperative hypoproteinemia. One of the reasons is that managing concomitant gastrointestinal surgery in these patients requires longer operating times, causing increased energy consumption and increased breakdown of plasma albumin [17] . Additionally, more uids need to be administered, leading to further dilution of plasma albumin [18] .…”
Section: Comparison Of Preoperative Data Between the Two Groupsmentioning
confidence: 99%